Factors Affecting Health Care Services Utilisation among Rural Population in Sabah, Malaysia - Adilius Manual; Mohd Yusof Ibrahim; Ho, Chong Mun; Norazah Mohd Suki (Penerbit UMS, 2024)
Malaysia has made significant strides in achieving universal health coverage since gaining independence. However, rural areas in Sabah still confront challenges in accessing adequate healthcare compared to Peninsula Malaysia. This study explores healthcare utilisation patterns among Sabah's rural populace, with a focus on identifying access determinants. Over four months, a household cross-sectional study interviewed 438 respondents, employing geographical units for random sample selection. The questionnaire used was adopted and pre-tested from the National Health and Morbidity Survey 2011 (Healthcare Demand Module). Descriptive statistics and logistic regression were utilised to analyse demographic characteristics and determinants of health utilisation among those reporting one or more diseases (n = 99). The findings underscored age and health limitations as significant predictors of healthcare usage. Despite commendable national health outcomes, resource allocation tends to favour secondary care over primary care in rural regions. Prioritising preventive care at the primary level could enhance overall health outcomes. Understanding healthcare utilisation in rural areas, especially those with heightened poverty rates, is crucial for refining tailored healthcare policies. This study fills a crucial gap in the literature, offering insights to shape effective healthcare interventions for underserved rural populations.